Impact of Fasting Blood Glucose Levels on Blood Pressure Parameters among Older Adults with Prediabetes - Thapanee Roengrit; Ruchada Sri-Amad; Nawiya Huipao; Suphawadee Phababpha; Piyapong Prasertsri (The Scientific World Journal, 2023)
Prediabetes mellitus (pre-DM) is defined as blood glucose levels higher than normal but lower than the threshold for diabetes mellitus (DM) diagnosis. Four-limb blood pressure (BP) differences can help identify a significant risk for cardiovascular diseases (CVDs). The current study aimed to determine the importance of BP and the ankle-brachial index (ABI) between two patient groups and the association between fasting blood glucose (FBG) levels and four-limb BP, ABI, interarm BP difference (IAD), and interleg BP difference (ILD). Moreover, the effect of cardiovascular risk factors on the development of pre-DM among older adults was evaluated. The participants were divided into the normal fasting glucose (NFG) and impaired fasting glucose (IFG) groups. Data on physical characteristics, lipid profiles, four-limb BP, ABI, IAD, ILD, and cardiovascular risk factors were assessed. The IFG group had a significantly higher systolic blood pressure (SBP) and pulse pressure than the NFG group (p < 0.05). SBP was significantly positively correlated with FBG levels (p < 0.05). The IFG group had a lower ABI than the NFG group (p < 0.05). However, there was no significant difference in terms of IAD and ILD between the two groups. Furthermore, hypertension (HT), metabolic syndrome (MetS), and dyslipidemia were significantly correlated with a high prevalence of prediabetes (p < 0.05). Individuals with prediabetes had a higher BP than those with normoglycemia. Prediabetes was correlated with HT, MetS, and dyslipidemia.